Sanksi Pidana bagi Pelaku Perbuatan Cabul terhadap Anak Dibawah Umur (Studi Kasus Putusan Nomor 29/Pid. Sus- Anak/2018/PN Dps) - I Putu Arta Setiawan; I Wayan Rideng; Ni Made Sukaryati Karma (Warmadewa Press, 2020)
Cases of molestation against children are rife today. This is a problem that becomes the duty of law enforcement officers and the community to fight. Abuse of children is carried out by offenders to fulfill thier lust and also because of sexual abnormalities. Related to this problem, law enforcement agencies in particular and the community must play an active role in making efforts to overcome these problems. Imposition of sanctions is a repressive effort that can be done to provide a deterrent effect for the perpetrators. Based on this problem, this study was conducted to describe how the legal protection of child victims of sexual abuse and how sanctions for perpetrators of sexual abuse of children. This study used a normative method, and research data are sourced from the opinions of legal scholars and the Law. The results of this study indicate that the government and the community are required to provide special protection such as rehabilitation efforts and keep victims from surrounding labeling or suffering from their identity as victims of sexual abuse or violence, as Article 64 Paragraph (1) and (3) of Law Number 23 Year 2002 JO Law Number 35 of 2014 concerning Child Protection regulates it. Based on Decision Number 29 / Pid. Sus-Anak / 2018 / PN Dps determined that the defendant BASID fulfilled the elements of the formulation in Article 82 paragraph (1) Jo Article 76 E of the Child Protection Act No. 35 of 2014 concerning amendments to the Law of the Republic of Indonesia Number 23 of 2002 concerning child protection and was sentenced to 13 (thirteen) years in prison along with job training at Mercy Indonesia Foundation Jalan Intan LC II Gang IV No.1 Gatot Subroto Denpasar for 6 (six) months as in a single indictment of the Public Prosecutor